2001
DOI: 10.1063/1.1333680
|View full text |Cite
|
Sign up to set email alerts
|

The ice/water interface: Molecular dynamics simulations of the basal, prism, {202̄1}, and {21̄1̄0} interfaces of ice Ih

Abstract: The structure and dynamics of the {0001} (basal), {101̄0} (prism), {202̄1}, and {21̄1̄0} ice Ih/water interfaces have been investigated using molecular dynamics and the flexible CF1 central force model of water. The translational order profile, the average density profile, and the diffusion profile have been calculated for all four interfaces as a function of distance normal to the interface. Dynamical molecular trajectories have been used to explore the loss of translational order from within the crystal regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
95
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(103 citation statements)
references
References 76 publications
7
95
1
Order By: Relevance
“…In addition, our recent studies have shown that there is significant charge inhomogeneity at the ice/water interface (54,55). The full charge distribution of SS3, or any polypeptide, interacts with the charge inhomogeneity that occurs naturally at any broad interface such as the ice/water interface.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, our recent studies have shown that there is significant charge inhomogeneity at the ice/water interface (54,55). The full charge distribution of SS3, or any polypeptide, interacts with the charge inhomogeneity that occurs naturally at any broad interface such as the ice/water interface.…”
Section: Discussionmentioning
confidence: 99%
“…146 On the one hand, preconfigured icelike water molecules on the IBS would facilitate ice-binding by inducing ice growth in the interfacial region between ice and bulk water, which is intrinsically disordered and approximately 10-20 Å thick. 147 On the other hand, waters near the non-IBS would be more distorted to prevent engulfment in the ice. The authors further proposed that the high entropic gain of merging the preorganized waters at the IBS with ice through this "zipper mechanism" would sufficiently reduce the free energy of the system to result in quasi-irreversible binding.…”
Section: Dual Function Of the Hydration Layermentioning
confidence: 99%
“…Although the adsorption-inhibition mechanism for ice growth inhibition has been generally accepted for Ͼ30 years, the mechanism by which AFPs recognize and bind ice has gone through several radical revisions without a consensus emerging. Recent simulations reveal that in contrast to other inorganic surfaces to which proteins may bind, an ice surface is disordered at the molecular level, with a 1-2-nm transition region separating ice from the surrounding bulk water solution (5).…”
mentioning
confidence: 99%